Implementasi Model Kewirausahaan Syariah Dalam Meningkatkan Kemandirian Ekonomi Panti Asuhan - Mustamin, Sitti Walida; Alfiani, Alfiani; Sri Wulandari; Vivin, Vivin; Sindi Nopitasari; Andi Hakim Rasyid; Ladi Elsa Gita B; Syamsidar, Syamsidar; Sakina Papalia; Herlina, Herlina; Nia Nafilah Andani (CV. ITTC INDONESIA, 2025)
This community service activity in orphanages aims to increase the understanding of the basic concepts of entrepreneurship among orphanage children, increase innovation and creativity in entrepreneurship as well as provide motivation and support for the development of a professional and productive entrepreneurial spirit as an effort to equip then with knowledge and training. In this case, sharia entrepreneurship includes an understanding of the basic of entrepreneurship in accordance with Islamic sharia, including starting an honest, proactive, productive, empowering, giving, humble, creative and innovative business. The development of this activity is carried out through a series of socialization of material delivery and craft making training to start a business. The evaluation showed an increase in the insight and knowledge of orphanage children with most of them expressing interest in becoming an entrepreneur. Through this effort, it is hoped that the children of the orphanage will participate in creating local economic growth and the economic independence of the young generation in creating new opportunities.